Democracy denied, youth participation and criminalizing digital dissent. (8th August 2016) - Bessant, Judith
ABSTRACT: Attention is given in this article to recent action by many liberal states to regulate and criminalize certain forms of political dissent reliant on new media. I ask how those working in the fields of youth studies and social science more generally might understand such processes of criminalizing political dissent involving young people digital media. I do this mindful of the prevailing concern about a 'crisis in democracy' said to be evident in the withdrawal by many young people from traditional forms of political engagement, and the need to encourage greater youth participation in democratic practices. A heuristic or guiding frame is developed to analyse how new laws, amendments to existing laws and other regulatory practices are being implemented to contain certain forms of political participation, performed in large part by young people. A case study of 'Distributed Denial of Service action' is offered to examine government responses to political practices which I argue constitute legitimate forms of protest and civil disobedience.